Kata-Kata Serapan Bahasa Sunda dari Al-Qur'an dalam Kitab Al-Amin - Firmansah Setia Budi (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2021)
Islam is Sundanese, Sundanese is Islam, a very well-known sentence among the Sundanese people. This term is a benchmark that since the entry of Islam in Tatar Sunda, Islam has contributed a lot in building Sundanese society. Among them is the enrichment of loanwords from the Koran. This study aims to determine what words are absorbed from the Koran and then become the language used by the Sundanese people in their daily lives. In addition, this study also intends to determine the semantic changes of the words adopted from the Koran. The method used in this research is the descriptive analysis method. The results showed that there were about 287 loanwords from Sundanese originating from the Koran. This research also shows that there are changes in the loan words mentioned above in semantic terms. Semantic change is divided into three, namely: a narrowing of meaning, an expansion of meaning and a change in meaning as a whole.